Affective disorders in comorbidity with alcohol addiction: clinical and dynamic features, social adaptation level of patients - S. N. Vasilieva; G. G. Simutkin; E. D. Schastnyy; E. V. Lebedeva; N. A. Bokhan (Бюллетень сибирской медицины, 2020)
The aim of the study was to reveal clinical and dynamic characteristics of affective disorders (AD) in comorbidity with alcohol addiction (AA).Materials and methods. 65 patients with affective disorders [22 women (34%) and 43 men (66%)] were examined. The main group included 34 patients aged 44.5 [36.0; 51.5] with affective disorders and comorbid alcohol addiction The comparison group included 31 patients aged 45 years [32; 52] with affective disorders without comorbid narcological pathology. Compared groups were matched by sex, age and nosological structure (p > 0.05). The following methods were used in the study: clinical and psychopathological, clinical follow-up, psychometric, statistical, as well as these psychometric scales: Clinical Global Impression (CGI), Hamilton Depression Rating Scale (HDRS-17), Hamilton Anxiety Rating Scale (HARS), Social Adaptation Self-evaluation Scale (SASS).Results. The comparative assessment of clinical and dynamic characteristics of affective disorders and social adaptation level was conducted. Chronology of occurrence of comorbid affective disorders and alcohol addiction was analyzed.Conclusion. Addition of alcohol addiction to affective disorders worsens the clinical and dynamic indices and social adaptation level of patients.